RTA THROUGH AHIMSA A GANDHIAN INTERPRETATION: . - Thottakara, Augustine (Journal of Dharma, 2002)
One of the most valuable and most original contributions of Indian thought and spirituality to the corpus of universal wisdom and to the reservoir of spiritual sciences of humanity is the concept of ahimsii. Hinduism proposed and practiced it as the supreme duty of humans iahimsii paramo dharmah); Buddhism and Jainism refined and made it the most sublime spiritual principle; great souls like Ashoka and Mahatma Gandhi rigorously practised and .powerfully preached it as a dynamic force that would guarantee peace and harmony in societal life and as an antidote to the culture of violence, discord and disharmony.